REUPLOAD FILM DI TELEGRAM: PERSPEKTIF UU HAK CIPTA DAN HUKUM BISNIS SYARIAH - Taufiqur Rahman , Tegar Taufiqur Rahman; Asi Islami, Trinah; Fitria, Norma (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
Reuploading movies on telegram needs to be investigated in terms of copyright and sharia business law as a form of legal protection. Copyright is part of the IPR branch that protects human creations in the fields of art, literature and science. Haqq al-ibtikar is a description of the thoughts produced by a scientist through the ability of thought and analysis is the first discovery or creation, which has not been put forward by scientists before. Copyright studies on video re-uploading via telegram based on sharia business law is still rarely studied. The purpose of this research is to find out the position of video reupload on Telegram from the perspective of UUHC and sharia business law perspective. Therefore, the formulation of the problem taken is (1) How is the re-uploading of movie videos on the telegram application, (2) What is the perspective of UUHC on the re-uploading of movie videos on the telegram application, and (3) How is the perspective of sharia business law on the re-uploading of movie videos on the tellegram application. The type of research used is normative juridical with a phenomenological, statutory and conceptual approach. Primary and secondary legal materials are used to answer the existing problems by using descriptive analytical methods. The results showed that (1) Video re-uploading in the Telegram application can be done through private and public channels, (2) Re-uploading in videos via Telegram has not applied the elements of article 40 letter m of the UUHC, (3) Video re-uploading via Telegram from the perspective of sharia business law has not fulfilled the principle of ibtikar rights so that it can be categorized as theft. Keywords: Movie, Telegram, Copyright, Haqq Al-Ibtikar, Sharia Business Law.